SAFETY OF MELOXICAM IN TREATMENT OF JUVENILE ARTHRITIS IN CHILDREN - E.S. Zholobova; Z.V. Gesheva; O.Yu. Konopel'ko; A.V. Meleshkina; O.S. Rozvadovskaya; T.N. Sergeeva ("Paediatrician" Publishers LLC, 2010)
The study estimated the safety of meloxicam in prolonged treatment of children with juvenile arthritis (JA). Clinical data and results of endoscopy of 50 patients with JA were analyzed. All patients were switched from diclofenac to meloxicam by different reasons. An estimation of hepatotoxicity of meloxicam compared to other non-steroidal anti-inflammatory drugs (NSAIDs) - diclofenac and nimesulid, was performed. The results of a study show that treatment with meloxicam decreases a risk of gastrointestinal adverse events in patients with JA. Hepatotoxicity rate of NSAIDs was 7,2%. Patients treated with meloxicam had lowest rate of transaminases increase. Key words: children, juvenile rheumatoid arthritis, juvenile chronic arthritis, NSAIDs, gastrotoxicity, hepatotoxicity. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(2):113-118)